PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI) BERBASIS AUTENTIK ASESMENT UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Fujiah, Fujiah; Prayogi, Saiful; Hidayat, Samsun (IKIP Mataram, 2016)
The objective of this research was to know the improvement of students critical thinking ability in MA Islahul Ummah NW Bunut Baok, academic year 2015/2016 by using PBI based on authentic assessment. This research used Classroom Action Research (CAR) and it consisted of two cycles. Each cycle consisted of planning, action, observation, and reflection. The data of student’s critical thinking ability was taken by giving student test, it was form of essay test. The results were obtainedseveral findings namely: 1) at first cycle: the mean score of students’ critical thinking abilitywas 54,41 and categorized into low category; 2) at second cycle:the mean score of students’ critical thinking ability was 85,29and categorizedintohigh category. Based on the results of this research can be concluded thatPBI based on authentic assessment can improve students’ critical thinkingability at the X grade students of MA. Islahul Ummah NW Bunut Baok, academic year 2015/2016.